Chemopreventive and chemotherapeutic properties of selected fruits endemic to Borneo: investigation on Mangifera pajang and Artocarpus odoratissimus - Abu Bakar, Mohd Fadzelly (2010)
Consumption of fruits and vegetables has been shown to reduce the risk of various types of cancer. Macro- and micro-nutrients as well as non-nutritive phytochemicals present in fruits and vegetables have been associated with this effect. This study was conducted to investigate the chemopreventive and chemotherapeutic potential of two types of fruits which are endemic to Borneo Island: Mangifera pajang (bambangan) and Artocarpus odoratissimus (tarap).